No News Is Bad News: Sensegiving Activities, Media Attention, and Venture Capital Funding of New Technology Organizations - Petkova, Antoaneta P.; Rindova, Violina P.; Gupta, Anil K. (Organization Science, 2013)
A significant body of research has examined how new organizations gain legitimacy and how gaining it affects their subsequent access to resources. Less attention has been given to the problem of how new organizations attract collective attention. Although related to legitimation, the problem of attracting attention is distinct, as attention and evaluation are distinct cognitive processes. In this study, we examine the allocation of collective attention to new organizations in a system of relationships, within which new organizations seek to attract attention through their sensegiving activities; the information properties of their sensegiving activities affect the level of attention they receive from different types of media; and media attention, in turn, increases their perceived value potential in the eyes of venture capital investors (VCs). We examine these relationships in a sample of 398 information-technology start-ups that have obtained different levels of venture capital funding. Our results show that new organizations that engage in more intense and diverse sensegiving activities attract higher levels of industry media attention and that these effects are enhanced by the human capital of their founders and leaders. Diverse sensegiving activities are also associated with higher levels of attention from the general media, but only the attention of specialized industry media is positively associated with the level of VC funding obtained. These findings extend current research on information intermediation and institutional legitimation by demonstrating that media attention early in the life of new organizations affects how they are valued by a well-informed expert audience, such as VCs. They also contribute to entrepreneurship research on the effects of new organizations’ strategies on their ability to secure resources and to research on VC funding decisions.